NEWLY-GRADUATED MEDICAL DOCTORS AS NEAR-PEER TUTORS FOR PREPARING NATIONAL LICENSING EXAMINATION: A CASE REPORT - Prattama Santoso Utomo; Arta Farmawati; James Degnan; Rachmadya Nur Hidayah; Rilani Riskiyana; Gandes Retno Rahayu (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2021)
Background: Medical students in Indonesia are required to pass a national licensing examination (e.g., UKMPPD) as a requirement of graduation and to obtain their certificate of competence. Medical schools prepared their students based on their needs and capacity. The preparation might use different teaching approaches. Undergraduate medicine program in Universitas Gadjah Mada conducts a national licensing examination preparation program facilitated by both faculty members and peer tutors. The peer tutors are newly graduated medical doctors who were recruited and trained. The use of trained peer tutors in a structured program to prepare high-stake examination such as a national examination is considered novel. This paper aims to describe a peer-assisted learning (PAL) approach used to prepare medical students in facing a national licensing examination.Case Discussion: A preparation program using faculty and peer tutors was deployed to prepare final-year medical students for facing the Indonesian national licensing examination. The ratio of sessions facilitated by faculty to peer tutors was 1:2. The preparation included CBT and OSCE training. Sessions with faculty used a medium to large class approach while sessions with peer tutors used a small to medium group approach. Through February 2020, 147 students have participated in the program. A questionnaire was developed to measure agreement that the program was successful and if the tutees were satisfied with various aspects of the program. The tutees responded with high rates of satisfaction to most items on the questionnaire (responses for all but one item ranged between 72.1% and 90.5% in favorable agreement or satisfaction). The one exception was CBT preparation where the level of satisfaction was lower (54.4% rated CBT favorably). Participants highly valued the involvement and the performance of peer tutors.Conclusion: The use of near-peer assisted learning for national licensing examination preparation has strong potential. Further study is required to investigate the impact of the peer-assisted national licensing examination preparation program on students’ achievement and clinical practice.